Strategi Pengendalian Persediaan Gas Acetylene pada Industri Migas (Studi Kasus pada PetroChina International Jabung Ltd.) - Nur Indrianti; Fajar Maulana Wijayanto (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Various materials and devices are needed to support production activities in the oil and gas industry. Therefore, optimal inventory strategy is required to satisfy the demand of the materials and devices with minimum inventory costs. This study deals with the evaluation of the inventory strategy of a private oil and gas company. As the object of the study, we considered acetylene inventory which is currently not managed properly. The strategy for acetylene inventory that has hitherto been implemented by the company is lot for lot ordering system in each period. In this study we applied Periodic Order Quantity, Wagner Whitin, and Silver Meal methods as alternative strategies for acetylene inventory control. The result of the study indicates that the Silver Meal method obtains optimal inventory schedule. It results in the lowest inventory costs compared to the other proposed methods and the current company’s strategy.